Effect of a Nurse-Led Intervention on Knowledge of the Modifiable Risk Behaviors of Cardiovascular Disease: A Randomized Controlled Trial - Okube, Okubatsion Tekeste; Kimani, Samuel T.; Mirie, Waithira (SAGE Open Nursing, 2023)
Abstract Introduction: Cardiovascular disease (CVD) has disproportionately burdened the low- and middle-income countries where awareness and detection rates remain very low. Interventions directed to promote the community’s awareness of CVD may help reduce the public’s exposure to behavioral risk factors. However, the effectiveness of interventions implemented through a nurse on knowledge of the modifiable behavioral risk factors and preventive measures of CVD has not been determined in Kenya. Objective: To establish the effect of a nurse-led intervention on knowledge of the modifiable risk behaviors of CVD in adults with metabolic syndrome (MetS) attending a mission-based hospital in Kenya. Methods: A two-armed parallel-group randomized controlled trial design was conducted among 352 adults aged 18–64 years with MetS. The participants were recruited from a faith-based hospital in Nairobi, Kenya and randomly allocated to either a nurse-led lifestyle intervention or a control group. The intervention group received a comprehensive health education inter vention using the World Health Organization (WHO) guideline recommendations for CVD control and prevention. Individuals in the control group were exposed to the usual CVD care according to hospital protocol. The duration of the intervention was 12 months. The primary outcome measure was a change in levels of knowledge on the modifiable risk fac tors and preventive measures of CVD. Outcome measures were assessed at baseline and at 15 months postintervention. Pre and postintervention difference in the level of knowledge between the two groups was determined using the chi-square test of independence. Results: The knowledge level of CVD risk factors and preventive measures was very low in both groups at baseline without significant difference. A significant improvement in the level of knowledge on CVD risk factors (78.2% vs. 30.4%, p < .001) and preventive measures (74.4% vs. 29.0%, p < .001) was observed in the intervention group relative to the control at the end-line. Conclusions: The nurse-led lifestyle intervention significantly improved participants’ level of knowledge on CVD risk factors and preventive measures. It is highly recommended that nurses incorporate routine health education interventions for patients with cardio-metabolic abnormalities.
Creative Commons Non Commercial CC BY-NC: This article is distributed under the terms of the Creative Commons Attribution NonCommercial 4.0 License (https://creativecommons.org/licenses/by-nc/4.0/) which permits non-commercial use, reproduction and distribution of the work without further permission provided the original work is attributed as specified on the SAGE and Open Access page (https://us.sagepub.com/en us/nam/open-access-at-sage).
Keywords: cardiovascular diseases; knowledge; preventive measures; risk factors